A single ion conductor polymer electrolyte and its preparation method and application
By grafting lithium bistrifluoromethanesulfonimide on the surface of the inorganic filler to form a single ion conductor, the problem of low lithium ion migration number of polymer-based lithium ion batteries is solved, and the cycle life and Coulomb efficiency of lithium ion batteries are significantly improved. .
Patent Information
- Application Number
- CN202111491263.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-12-08
AI Technical Summary
The number of lithium ion migrations of existing polymer-based lithium ion batteries is low, resulting in the concentration polarization problem of anion aggregation, affecting the cycle life and Coulomb efficiency of lithium ion batteries.
By grafting lithium bistrifluoromethanesulfonimide on the surface of the inorganic filler, a single ion conductor is formed, which limits the migration of anions, thereby increasing the migration number of lithium ions.
It effectively improves the Coulomb efficiency and cycle life of lithium-ion batteries, which are specifically manifested as 68 to 78 cycles in 25℃ and 76 to 86 cycles in 45℃.
Smart Images

Figure CN114204115B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytes, and in particular relates to a single ion conductor polymer electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used due to their environmental friendliness and excellent cycle performance. Electrolytes, as key components of lithium-ion batteries, are closely related to battery cycle life, safety, capacity and other performance. Currently, the most widely used organic liquid electrolytes on the market are prone to organic solvent leakage, combustion and explosion, which poses a great safety hazard. Therefore, solid electrolytes have become a hot topic of research.
[0003] Solid electrolytes mainly include three categories: inorganic solid electrolytes, polymer solid electrolytes and organic / inorganic composite solid electrolytes. For the research of all-solid-state lithium secondary batteries, there are two main categories according to the electrolyte: one is a lithium secondary battery composed of an organic polymer electrolyte, also known as a polymer all-solid-state lithium battery; the other is a lithium secondary battery composed of an inorganic solid electrolyte, also known as an inorganic all-solid-state lithium battery. CN112062991A discloses a method for preparing an organic-inorganic solid electrolyte, which uses a high-temperature solid-phase synthesis method, with lithium fluoride and lithium hydroxide as raw materials, synthesized in a vacuum, and then mixed with organic polyethylene oxide to form a solid electrolyte film. At the end of the reaction, the molten product in the quartz tube is quickly cooled to room temperature, resulting in different textures and grain boundary morphologies. Continuous heating and removal of water under high vacuum promote chemical equilibrium. The invention is simple to prepare, short in time, and highly controllable. It can be used to produce high-quality lithium oxyfluoride materials, suitable for large-scale quantitative preparation, short in time, and high in purity. However, most polymer matrices are similar to liquid electrolytes, are dual ion conductors, and have a low lithium ion migration number (t Li + <0.5), during the charge and discharge process, anions accumulate on the positive electrode surface causing concentration polarization problems, which affects the cycle life of lithium-ion batteries.
[0004] Therefore, in order to increase the lithium ion migration number of the polymer matrix, solve the concentration polarization problem generated by anions, and improve the coulombic efficiency and cycle life of lithium ion batteries, it is an urgent problem to develop a single-ion conductor polymer electrolyte with a higher lithium ion migration number to address the problem of low polymer-based lithium ion migration number. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention aims to provide a single-ion conductor polymer electrolyte and a preparation method and application thereof. The single-ion conductor polymer electrolyte comprises a combination of a single-ion conductor, an oxide solid electrolyte and a polymer matrix; the single-ion conductor comprises an inorganic filler and lithium bis(trifluoromethanesulfonyl imide) grafted on the surface of the inorganic filler via a sulfonyl chloride group; by grafting bis(trifluoromethanesulfonyl imide) onto the inorganic filler skeleton, the migration of anions therein is restricted, thereby effectively increasing the migration number of lithium ions in the electrolyte, thereby improving the coulombic efficiency and cycle life of the lithium ion battery.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a single ion conductor polymer electrolyte, the single ion conductor polymer electrolyte comprising a combination of a single ion conductor, an oxide solid electrolyte and a polymer matrix;
[0008] The single ion conductor includes an inorganic filler and lithium bis(trifluoromethanesulfonyl)imide grafted onto the surface of the inorganic filler via a sulfonyl chloride group.
[0009] The single ion conductor polymer electrolyte provided by the present invention comprises a combination of a single ion conductor, an oxide solid electrolyte and a polymer matrix; the single ion conductor comprises an inorganic filler and lithium bis(trifluoromethanesulfonyl)imide grafted on the surface thereof via a sulfonyl chloride group; the lithium bis(trifluoromethanesulfonyl)imide is fixed on the inorganic filler skeleton, thereby limiting the migration of anions therein, effectively solving the problem of concentration polarization of anions, thereby increasing the migration number of lithium ions in the polymer electrolyte, so that the coulomb efficiency and cycle performance of a lithium ion solid-state battery comprising the single ion conductor polymer electrolyte are effectively improved.
[0010] Preferably, the single ion conductor is prepared by the following method, which comprises the following steps:
[0011] (A1) reacting an inorganic filler and methanesulfonyl chloride in a solvent to obtain a modified inorganic filler;
[0012] (A2) reacting the modified inorganic filler obtained in step (A1) with lithium bis(trifluoromethanesulfonyl imide) in a solvent to obtain the single ion conductor.
[0013] In the present invention, the single ion conductor is prepared in two steps. First, an inorganic filler and methanesulfonyl chloride are reacted to obtain a single ion conductor as shown in the schematic diagram. Figure 1 The sulfonyl chloride modified inorganic filler shown in the figure; then the obtained sulfonyl chloride modified inorganic filler is directly mixed with lithium bis(trifluoromethanesulfonyl imide) to obtain a schematic diagram as shown in Figure 2 Single ion conductors of inorganic fillers modified with lithium trifluoromethanebissulfonyl imide are shown.
[0014] Preferably, the inorganic filler in step (A1) comprises any one of SiO2, halloysite, mullite, serpentine, kaolinite, aluminum silicate, magnesium silicate, magnesium strontium silicate or nickel silicate, or a combination of at least two thereof.
[0015] Preferably, in step (A1), the mass ratio of the inorganic filler to methanesulfonyl chloride is 1:(2-10), for example, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9.
[0016] Preferably, the solvent in step (A1) comprises toluene.
[0017] Preferably, the reaction time of step (A1) is 8 to 12 h, for example, 8.4 h, 8.8 h, 9.2 h, 9.6 h, 10 h, 10.4 h, 10.8 h, 11.2 h or 11.6 h.
[0018] Preferably, the reaction temperature in step (A1) is 60-80°C, for example, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C or 78°C.
[0019] Preferably, the mass ratio of the modified inorganic filler to lithium bis(trifluoromethanesulfonyl)imide in step (A2) is 1:(2-10), for example, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9.
[0020] Preferably, the solvent in step (A2) comprises acetonitrile.
[0021] Preferably, the reaction time of step (A2) is 12 to 24 h, for example, 14 h, 16 h, 18 h, 20 h, 21 h, 22 h or 23 h.
[0022] As a preferred technical solution of the present invention, the preparation method of the single ion conductor comprises the following steps:
[0023] (A1) reacting an inorganic filler and methanesulfonyl chloride in a mass ratio of 1:(2-10) in a solvent at 60-80° C. for 8-12 hours to obtain a modified inorganic filler;
[0024] (A2) reacting the modified inorganic filler obtained in step (A1), lithium bis(trifluoromethanesulfonyl imide) and bipyridine in a solvent for 12 to 24 hours to obtain the single ion conductor.
[0025] Preferably, the mass ratio of the single ion conductor to the oxide solid electrolyte is (1-3):1, for example, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1 or 2.8:1, etc.
[0026] As a preferred technical solution of the present invention, the mass ratio of the single ion conductor to the oxide solid electrolyte in the single ion conductor polymer solid electrolyte provided by the present invention is (1-3):1. If the amount of the single ion conductor is too much, the tensile strength of the electrolyte membrane formed by the obtained single ion conductor polymer electrolyte will be reduced; if the amount of the oxide solid electrolyte is too much, the ion migration number of the electrolyte membrane formed by the obtained single ion conductor polymer electrolyte will be reduced.
[0027] Preferably, the oxide solid electrolyte includes any one of a garnet-type oxide solid electrolyte, a NaSICON-type oxide solid electrolyte or a perovskite-type oxide solid electrolyte, or a combination of at least two thereof.
[0028] Preferably, the mass ratio of the single ion conductor to the polymer matrix is (0.1-0.5):1, for example, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1 or 0.45:1, etc.
[0029] Preferably, the polymer matrix includes any one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate or polyacrylonitrile, or a combination of at least two thereof.
[0030] In a second aspect, the present invention provides a method for preparing the single ion conductor polymer electrolyte as described in the first aspect, the preparation method comprising the following steps:
[0031] (1) mixing a single ion conductor and an oxide solid electrolyte in an organic solvent to obtain a suspension;
[0032] (2) Mixing the polymer matrix and the suspension obtained in step (1) to obtain the single ion conductor polymer electrolyte.
[0033] Preferably, the organic solvent in step (1) comprises any one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or acetonitrile.
[0034] Preferably, the mixing in step (1) is carried out under ultrasonic conditions.
[0035] Preferably, the mixing time in step (1) is 5 to 30 min, for example, 7 min, 9 min, 11 min, 13 min, 15 min, 17 min, 19 min, 21 min, 23 min, 25 min, 27 min or 29 min, etc.
[0036] Preferably, the mixing in step (2) is carried out in a planetary mixer.
[0037] Preferably, the mixing time in step (2) is 1 to 3 h, for example, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h or 2.8 h.
[0038] In a third aspect, the present invention provides a lithium-ion solid-state battery, comprising the single-ion conductor polymer solid electrolyte, a positive electrode sheet, a negative electrode sheet and an aluminum-plastic film as described in the first aspect.
[0039] Preferably, the positive electrode material in the positive electrode sheet includes any one of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium-rich manganese-based material or spinel lithium manganese oxide, or a combination of at least two thereof.
[0040] Preferably, the negative electrode material in the negative electrode sheet includes any one of graphite, amorphous carbon, lithium titanate, SiOx / C composite material or Sn-based composite material, or a combination of at least two thereof.
[0041] In a fourth aspect, the present invention provides a method for preparing a lithium-ion solid-state battery as described in the third aspect, the preparation method comprising the following steps:
[0042] (B1) coating a single ion conductor polymer electrolyte on the surface of the positive electrode sheet to obtain a composite positive electrode; coating a single ion conductor polymer electrolyte on the surface of the negative electrode sheet to obtain a composite negative electrode;
[0043] (B2) stacking the composite positive electrode and the composite negative electrode obtained in step (B1), and encapsulating them with an aluminum-plastic film to obtain the lithium-ion solid-state battery.
[0044] Preferably, step (B1) further includes a drying step after coating on the surface of the positive electrode sheet and coating on the surface of the negative electrode sheet.
[0045] Preferably, the drying time is 8 to 12 hours, for example, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours or 11.5 hours.
[0046] Preferably, the drying temperature is 50-70°C, for example, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C or 68°C.
[0047] Preferably, after the drying is completed, the thickness of the positive electrode sheet surface coating and the negative electrode sheet surface coating is independently 20 to 40 μm, for example, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm or 38 μm.
[0048] Preferably, after the packaging in step (B2), the steps of vacuuming, heat sealing, hot pressing and cold pressing are also included.
[0049] Preferably, the heat sealing temperature is 180-200°C, for example, 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C or 198°C.
[0050] Preferably, the heat sealing pressure is 0.1-1 MPa, for example, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa or 0.9 MPa.
[0051] Preferably, the heat sealing time is 5 to 10 s, for example, 5.5 s, 6 s, 6.5 s, 7 s, 7.5 s, 8 s, 8.5 s, 9 s or 9.5 s.
[0052] Preferably, the temperature of the hot pressing is 80-100°C, for example, 82°C, 84°C, 86°C, 88°C, 100°C, 102°C, 104°C, 106°C or 108°C.
[0053] Preferably, the pressure of the hot pressing and the cold pressing is independently 0.1-0.5 MPa, such as 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa or 0.45 MPa.
[0054] Preferably, the time of the hot pressing and the cold pressing is independently 20 to 300 s, for example, 50 s, 80 s, 110 s, 140 s, 170 s, 200 s, 230 s, 260 s or 290 s.
[0055] Preferably, the temperature of the cold pressing is 20-30°C, for example, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C or 29°C.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The single ion conductor polymer electrolyte provided by the present invention comprises a combination of a single ion conductor, an oxide solid electrolyte and a polymer matrix; the single ion conductor comprises an inorganic filler and bis(trifluoromethanesulfonyl)imide grafted on the surface of the inorganic filler via a sulfonyl chloride group; by fixing bis(trifluoromethanesulfonyl)imide on the inorganic filler skeleton, the migration of anions therein is restricted, and the concentration polarization problem generated by anions can be effectively solved, thereby effectively improving the lithium ion migration number. Specifically, the ion migration number of the single ion conductor polymer electrolyte provided by the present invention is 0.4-0.72, and the ionic conductivity is 7.46×10 -5 ~2.42×10 -4S / cm, so that the coulombic efficiency and cycle performance of the lithium ion solid-state battery containing the single-ion conductor polymer electrolyte are effectively improved. Specifically, the lithium ion solid-state battery containing the single-ion conductor polymer electrolyte provided by the present invention has a cycle number of 68 to 78 times at 25°C and a cycle number of 76 to 86 times at 45°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a schematic diagram of the structure of the inorganic filler modified with sulfonyl chloride in Preparation Example 1;
[0059] Figure 2 This is a schematic diagram of the structure of the single ion conductor of the inorganic filler modified by lithium trifluoromethanebissulfonyl imide obtained in Preparation Example 1. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0061] Preparation Example 1
[0062] A single ion conductor, the preparation method of which comprises the following steps:
[0063] (1) At 70°C, SiO2 and methanesulfonyl chloride in a mass ratio of 1:5 were reacted in toluene for 10 h to obtain the result shown in the schematic diagram. Figure 1 The sulfonyl chloride-modified inorganic filler shown;
[0064] (2) The modified SiO2 obtained in step (A1) and lithium bis(trifluoromethanesulfonyl imide) were reacted in acetonitrile at a mass ratio of 1:5 for 20 h to obtain a product as shown in the schematic diagram. Figure 2 Single ion conductors of inorganic fillers modified with lithium trifluoromethanebissulfonyl imide are shown.
[0065] Preparation Example 2
[0066] A single ion conductor, the preparation method of which comprises the following steps:
[0067] (1) At 60° C., halloysite and methanesulfonyl chloride in a mass ratio of 1:2 were reacted in toluene for 12 h to obtain modified halloysite;
[0068] (2) The modified halloysite obtained in step (A1) and lithium bis(trifluoromethanesulfonyl)imide were reacted together in acetonitrile at a mass ratio of 1:2 for 24 hours to obtain the single ion conductor.
[0069] Preparation Example 3
[0070] A single ion conductor, the preparation method of which comprises the following steps:
[0071] (1) At 80° C., kaolinite and methanesulfonyl chloride in a mass ratio of 1:10 were reacted in toluene for 8 h to obtain modified kaolinite;
[0072] (2) The modified kaolinite obtained in step (A1) and lithium bis(trifluoromethanesulfonyl)imide were reacted in acetonitrile at a mass ratio of 1:10 for 12 hours to obtain the single ion conductor.
[0073] Example 1
[0074] A single ion conductor polymer electrolyte, comprising a single ion conductor (Preparation Example 1) with a mass ratio of 2:1:10, a garnet oxide solid electrolyte (LLZO) and polyethylene oxide (Aladdin, 68441-17-8);
[0075] The preparation method thereof comprises the following steps:
[0076] (1) placing a single ion conductor and a garnet oxide solid electrolyte in N-methylpyrrolidone and dispersing them by ultrasonication for 15 minutes to obtain a suspension;
[0077] (2) Mixing polyethylene oxide and the suspension obtained in step (1), stirring for 2 hours using a planetary mixer, to obtain the single ion conductor polymer electrolyte.
[0078] Example 2
[0079] A single ion conductor polymer electrolyte, comprising a single ion conductor (Preparation Example 2), a NaSICON type oxide solid electrolyte (LATP) and polyvinylidene fluoride (Arkema, HSV761) in a mass ratio of 1:1:10;
[0080] The preparation method thereof comprises the following steps:
[0081] (1) placing a single ion conductor and a NaSICON type oxide solid electrolyte in N,N-dimethylformamide and dispersing them by ultrasonication for 5 minutes to obtain a suspension;
[0082] (2) Mixing polyvinylidene fluoride and the suspension obtained in step (1), and stirring for 1 hour using a planetary mixer to obtain the single ion conductor polymer electrolyte.
[0083] Example 3
[0084] A single ion conductor polymer electrolyte, comprising a single ion conductor (Preparation Example 3) with a mass ratio of 3:1:20, a perovskite oxide solid electrolyte (LLTO) and polyvinylidene fluoride-hexafluoropropylene (Solvay, 21510);
[0085] The preparation method thereof comprises the following steps:
[0086] (1) placing a single ion conductor and a perovskite oxide solid electrolyte in acetonitrile and dispersing them by ultrasonication for 30 minutes to obtain a suspension;
[0087] (2) The polyvinylidene fluoride-hexafluoropropylene and the suspension obtained in step (1) are mixed, and stirred for 3 hours by a planetary mixer to obtain the single ion conductor polymer electrolyte.
[0088] Example 4
[0089] A single ion conductor polymer electrolyte is different from Example 1 only in that the mass ratio of the single ion conductor to the garnet oxide solid electrolyte is 0.5:1, and other components, amounts and preparation methods are the same as those in Example 1.
[0090] Example 5
[0091] A single ion conductor polymer electrolyte is different from Example 1 only in that the mass ratio of the single ion conductor to the garnet oxide solid electrolyte is 4:1, and other components, amounts and preparation methods are the same as those in Example 1.
[0092] Comparative Example 1
[0093] A polymer electrolyte comprising SiO2, lithium bis(trifluoromethanesulfonyl imide), garnet-type oxide solid electrolyte and polyethylene oxide (Aladdin, 68441-17-8) in a mass ratio of 2:2:1:10;
[0094] The preparation method comprises: dispersing SiO2 in N-methylpyrrolidone for 15 minutes, adding polyethylene oxide and garnet oxide solid electrolyte and mixing them in a planetary mixer for 30 minutes, adding bistrifluoromethanesulfonyl imide lithium and mixing them in a planetary mixer for 1 hour to obtain the polymer electrolyte.
[0095] Performance Test:
[0096] (1) Ionic conductivity test: Make a symmetrical battery with stainless steel sheets, with the negative electrode shell opening facing upwards, place the spring sheet and stainless steel gasket in the middle of the negative electrode shell respectively, clamp the solid electrolyte membrane to cover the stainless steel gasket, and clamp another stainless steel sheet to cover the solid electrolyte membrane, and strictly align them, and finally clamp the positive electrode shell to cover it, and then use tweezers to place the button battery with the negative electrode facing upwards on the button battery sealing mold, adjust the pressure to 10MPa, and hold the pressure for 5s before assembling into a button battery. Use an electrochemical workstation for EIS testing, with a frequency range of 106 -1Hz, amplitude 5mV, the conductivity of electrolyte membrane ions is calculated using the formula ionic conductivity σ = L / (R×A), where L is the thickness of the electrolyte membrane, A is the effective area of the electrolyte membrane, and R is the bulk resistance of the electrolyte membrane. The resistance value at the intersection of the EIS curve and the real axis is the ionic conductivity.
[0097] (2) Ion migration number test: Make a lithium-lithium symmetrical battery with the negative electrode shell opening facing upward. Place the spring sheet and the gasket in the middle of the negative electrode shell in turn. Clamp the lithium sheet and place it on the steel gasket. Align them strictly. Clamp the solid electrolyte membrane to cover the lithium sheet. Clamp another lithium sheet to cover the solid electrolyte membrane. Align them strictly. Finally, clamp the gasket to cover the lithium sheet. Align them strictly. Clamp the positive electrode shell to cover it. Finally, use tweezers to place the button battery with the negative electrode facing upward on the button battery sealing mold. Adjust the pressure to 10 MPa and maintain the pressure for 5 seconds to complete the assembly of the lithium-lithium symmetrical battery. Use an electrochemical workstation for DC polarization and test the EIS before and after battery polarization. Use the formula ion migration number t + =[I×(ΔV-I0R0)] / [I0×(ΔV-IR)] calculates the ion migration number of the electrolyte membrane, I0 is the intercept point of the y-axis during polarization, I is the steady-state value during polarization, R0 is the impedance value before polarization, R is the impedance value after polarization, and ΔV is the bias voltage.
[0098] (3) Cycle performance test: A lithium-ion solid-state battery was prepared, and a single-ion conductor polymer electrolyte was coated on the surface of a positive electrode sheet (the positive electrode sheet comprises: 97 wt% NCM ternary material, 1 wt% carbon black, 1 wt% PVDF and an aluminum foil with a thickness of 12 μm), and dried at 60°C for 10 h to obtain a composite positive electrode with a coating thickness of 30 μm; a single-ion conductor polymer electrolyte was coated on the surface of a negative electrode sheet (the negative electrode sheet comprises: 80 wt% graphite, 15 wt% silicon-oxygen active material, 2 wt% carbon nanotubes and carbon black, 3 wt% PAA and a copper foil with a thickness of 8 μm), and dried at 60°C for 10 h, and obtain a composite negative electrode with a coating thickness of 30 μm; the obtained composite positive electrode and the composite negative electrode are superimposed to make the capacity of the obtained soft-pack solid-state battery be 1200 mA / h, and the battery is packaged with an aluminum-plastic film, vacuumed, heat-sealed at 190°C and 0.5 MPa for 7s, hot-pressed at 90°C and 0.25 MPa for 150s, and cold-pressed at 25°C and 0.25 MPa for 150s to obtain a lithium-ion solid-state battery; the obtained lithium-ion solid-state battery is tested at 45°C and 25°C respectively, and the number of cycles when the capacity of the solid-state battery reaches 80% under 0.2C conditions is the cycle performance.
[0099] The single ion conductor polymer electrolytes obtained in Examples 1 to 5 and Comparative Example 1 were tested according to the above test method. The test results are shown in Table 1:
[0100] Table 1
[0101]
[0102]
[0103] According to the data in Table 1, it can be seen that the single ion conductor polymer electrolyte provided by the present invention has a high ion migration number and a high ion conductivity, and the lithium ion battery prepared by using the single ion conductor polymer electrolyte has a relatively excellent cycle performance. Specifically, the ion migration number of the single ion conductor polymer electrolyte obtained in Examples 1 to 5 is 0.4 to 0.72, and the ion conductivity is 7.46×10 -5 ~2.42×10 -4 S / cm, the number of cycles at 25°C is 68 to 78 times, and the number of cycles at 45°C is 76 to 86 times.
[0104] By comparing Example 1 and Comparative Example 1, it can be found that the ion migration number and ion conductivity of the general polymer solid electrolyte provided in the prior art are low, and thus the number of cycles of the prepared lithium ion battery is low, indicating that the cycle performance is poor.
[0105] Further comparison of Example 1 and Examples 4-5 shows that a low addition amount of the single ion conductor in the single ion conductor polymer electrolyte (Example 4) and a low addition amount of the garnet-type oxide solid electrolyte (Example 5) will affect the cycle performance of the prepared lithium ion battery.
[0106] The applicant declares that the present invention illustrates a single ion conductor polymer electrolyte and its preparation method and application through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A single ion conductor polymer electrolyte, characterized in that: The single ion conductor polymer electrolyte comprises a combination of a single ion conductor, an oxide solid electrolyte and a polymer matrix; The single ion conductor comprises an inorganic filler and lithium bis(trifluoromethanesulfonylimide) grafted onto the surface of the inorganic filler via a sulfonyl chloride group; The single ion conductor is prepared by the following method, which comprises the following steps: (A1) reacting an inorganic filler and methanesulfonyl chloride in a solvent to obtain a modified inorganic filler; (A2) reacting the modified inorganic filler obtained in step (A1) with lithium bis(trifluoromethanesulfonyl imide) in a solvent to obtain the single ion conductor; The mass ratio of the inorganic filler to methanesulfonyl chloride in step (A1) is 1:(2-10); The mass ratio of the modified inorganic filler to lithium bis(trifluoromethanesulfonyl)imide in step (A2) is 1:(2-10); The mass ratio of the single ion conductor to the oxide solid electrolyte is (1-3):1; The oxide solid electrolyte includes any one of a garnet-type oxide solid electrolyte, a NaSICON-type oxide solid electrolyte or a perovskite-type oxide solid electrolyte, or a combination of at least two thereof.
2. The single ion conductor polymer electrolyte according to claim 1, characterized in that The inorganic filler in step (A1) includes any one of SiO2, halloysite, mullite, serpentine, kaolinite, aluminum silicate, magnesium silicate, magnesium strontium silicate or nickel silicate, or a combination of at least two thereof.
3. The single ion conductor polymer electrolyte according to claim 1, characterized in that The solvent in step (A1) includes toluene.
4. The single ion conductor polymer electrolyte according to claim 1, characterized in that The reaction time of step (A1) is 8 to 12 h.
5. The single ion conductor polymer electrolyte according to claim 1, characterized in that: The reaction temperature in step (A1) is 60-80°C.
6. The single ion conductor polymer electrolyte according to claim 1, characterized in that The solvent in step (A2) comprises acetonitrile.
7. The single ion conductor polymer electrolyte according to claim 1, characterized in that The reaction time of step (A2) is 12 to 24 hours.
8. The single ion conductor polymer electrolyte according to claim 1, characterized in that: The mass ratio of the single ion conductor to the polymer matrix is (0.1-0.5):
1.
9. The single ion conductor polymer electrolyte according to claim 1, characterized in that: The polymer matrix includes any one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate or polyacrylonitrile, or a combination of at least two thereof.
10. A method for preparing a single ion conductor polymer electrolyte as claimed in any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: (1) Mixing a single ion conductor and an oxide solid electrolyte in an organic solvent to obtain a suspension; (2) Mixing the polymer matrix and the suspension obtained in step (1) to obtain the single ion conductor polymer electrolyte.
11. The preparation method according to claim 10, characterized in that: The organic solvent in step (1) includes N -Methylpyrrolidone, N,N -dimethylformamide, N,N - Either dimethylacetamide or acetonitrile.
12. The preparation method according to claim 10, characterized in that: The mixing in step (1) is carried out under ultrasonic conditions.
13. The preparation method according to claim 10, characterized in that: The mixing time in step (1) is 5 to 30 minutes.
14. The preparation method according to claim 10, characterized in that: The mixing in step (2) is carried out in a planetary mixer.
15. The preparation method according to claim 10, characterized in that: The mixing time in step (2) is 1 to 3 hours.
16. A lithium-ion solid-state battery, characterized in that: The lithium-ion solid-state battery comprises the single-ion conductor polymer solid electrolyte according to any one of claims 1 to 9, a positive electrode sheet, a negative electrode sheet and an aluminum-plastic film.
17. The lithium-ion solid-state battery according to claim 16, characterized in that: The positive electrode material in the positive electrode sheet includes any one of lithium cobalt oxide, ternary material, lithium iron phosphate, lithium-rich manganese-based material or spinel lithium manganese oxide, or a combination of at least two thereof.
18. The lithium-ion solid-state battery according to claim 16, characterized in that: The negative electrode material in the negative electrode sheet includes any one of graphite, amorphous carbon, lithium titanate, SiOx / C composite material or Sn-based composite material, or a combination of at least two thereof.
19. A method for preparing a lithium ion solid-state battery according to any one of claims 16 to 18, characterized in that: The preparation method comprises the following steps: (B1) coating a single ion conductor polymer electrolyte on the surface of a positive electrode sheet to obtain a composite positive electrode; coating a single ion conductor polymer electrolyte on the surface of a negative electrode sheet to obtain a composite negative electrode; (B2) The composite positive electrode and the composite negative electrode obtained in step (B1) are stacked and packaged with an aluminum-plastic film to obtain the lithium-ion solid-state battery.
20. The preparation method according to claim 19, characterized in that: The step (B1) further comprises a drying step after coating on the surface of the positive electrode sheet and coating on the surface of the negative electrode sheet.
21. The preparation method according to claim 20, characterized in that: The drying time is 8 to 12 hours.
22. The preparation method according to claim 20, characterized in that: The drying temperature is 50-70°C.
23. The preparation method according to claim 20, characterized in that: After the drying is completed, the thickness of the positive electrode surface coating and the negative electrode surface coating are independently 20-40 μm.
24. The preparation method according to claim 19, characterized in that: After the packaging in step (B2) is completed, the steps of vacuuming, heat sealing, hot pressing and cold pressing are also included.
25. The preparation method according to claim 24, characterized in that: The heat sealing temperature is 180-200°C.
26. The preparation method according to claim 24, characterized in that: The heat sealing pressure is 0.1-1 MPa.
27. The preparation method according to claim 24, characterized in that: The heat sealing time is 5 to 10 s.
28. The preparation method according to claim 24, characterized in that: The temperature of the hot pressing is 80-100°C.
29. The preparation method according to claim 24, characterized in that: The pressures of the hot pressing and cold pressing are independently 0.1-0.5 MPa.
30. The preparation method according to claim 24, characterized in that: The time of the hot pressing and the cold pressing is independently 20 to 300 s.
31. The preparation method according to claim 24, characterized in that: The temperature of the cold pressing is 20-30°C.
Citation Information
Patent Citations
Preparation method of organic-inorganic solid electrolyte
CN112062991A
Polyimide single-ion polymer, preparation method thereof and solid polymer electrolyte membrane
CN111548490A
Cross-linked network SiO2 composite single-ion conductor electrolyte, and preparation method and application thereof
CN112952202A
Solid polymer electrolyte and Li ion battery comprising the same
KR1020170060225A